Incidence and Risk Factors for Postoperative Venous Thromboembolic Events in Patients Undergoing Cervical Spine Surgery. Issue 8 (October 2021) - Bui, Annelise; Lashkari, Nassim; Formanek, Blake; Wang, Jeffrey C.; Buser, Zorica; Liu, John C.
Abstract : Study Design: This was a retrospective database study. Objective: The objective of this study was to investigate preoperative risk factors and incidence of venous thromboembolic events (VTEs) after cervical spine surgery. Summary of Background Data: VTEs are preventable complications that may occur after spinal procedures. Globally, VTEs account for a major cause of morbidity and mortality. Preoperative risks factors associated with increased VTE incidence after cervical spine surgery have not been well-characterized. Materials and Methods: Patients undergoing anterior cervical discectomy and fusion (ACDF); posterior cervical fusion (PCF); discectomy; and decompression from 2007 to 2017 were identified using the PearlDiver Database. International Classification of Diseases (ICD) Ninth and 10th Revision codes were used to identify VTEs at 1 week, 1 month, and 3 months postoperative as well as preoperative risk factors. Results: Risk factors with the highest incidence of VTE at 3 months were primary coagulation disorder [ACDF=7.82%, odds ratio (OR)=3.96; decompression=11.24%, OR=3.03], central venous line (ACDF=5.68%, OR=2.11; PCF=12.58%, OR=2.27; decompression=10.17%, OR=2.80) and extremity paralysis (ACDF=6.59%, OR=2.73; PCF=18.80%, OR=2.99; decompression=11.86, OR=3.74). VTE incidence at 3 months for populations with these risks was significant for all surgery types ( P <0.001) with the exception of patients with primary coagulation disorder who underwent PCF. Tobacco use had the lowest VTE incidence for all surgery types. Conclusions: The total cumulative incidence of VTEs at 3-month follow-up was 3.10%, with the highest incidence of VTEs occurring within the first postoperative week (0.65% at 1 wk, 0.61% at 1 mo, 0.53% at 3 mo for ACDF; 2.56% at 1 wk, 1.93% at 1 mo, 1.45% at 3 mo for PCF; 1.37% at 1 wk, 0.93% at 1 mo, 0.91% at 3 mo for decompression). Several preoperative risk factors were found to be significant predictors for postoperative VTEs and can be used to suggest those at increased risk as well as decrease the incidence of preventable VTEs after cervical spine surgery. Level of Evidence: Level III.